The relationship between quality and quantity of antenatal care services and stunting in children 24–59 months of age - Aulia Pramesti; Hartati Eko Wardani; Tika Dwi Tama; Anindya Hapsari (Public Health and Occupational Safety Journal, 2025)
Background: Stunting is a chronic nutritional problem whose causes include unmet nutrition in pregnant women, lack of infant nutritional intake, and socioeconomic conditions. Dinoyo Health Center covers an area with a high stunting rate in Malang City, particularly Lowokwaru District. Previous research stated that the dominant factor causing stunting in toddlers is antenatal care (ANC). Objectives: This study aims to determine whether stunting in toddlers in the Dinoyo Community Health Center area is caused by the quality and quantity of ANC. Methods: The research method is observational analytic with a case-control design using a retrospective approach. The population was 1643 mothers taken from three villages: Tlogomas, Dinoyo, and Sumbersari. The research sample amounted to 69 people using purpose sampling. The research was conducted in February - March 2023. Quality measurement was based on a minimum 10T service standard, while quantity measurement was based on a minimum frequency of 4 visits using a checklist sheet instrument and MCH book with Chi-Square analysis. Results: The results obtained for ANC quality with stunting p-value = 0.609 with OR value = 1.30 (95% CI: 0.47-3.55), while ANC quantity with stunting p-value = 0.864 with OR value = 1.09 (95% CI: 0.40-2.97). Conclusions: It is concluded that the quality and quantity of antenatal care have no association with the incidence of stunting in children under 24-59 months in the Dinoyo Community Health Center (Puskesmas) area. These findings highlight the need for multifactor interventions beyond ANC to reduce stunting, such as improved maternal nutrition and environmental sanitation.